Effect of agitation rate on butanol and ethanol production from palm oil mill effluent by Clostridium acetobutylicum - Zuriana, Sidi Ahmad (2010)
Malaysia is world largest palm oil producing country. The crude palm oil mill releases liquid effluent known as palm oil mill effluent (POME). These waste result in a significant environmental problem if not dispose in proper manner. The objective of this research is to study the effect of agitation rate on butanol and ethanol production from palm oil mill effluent by Clostridium acetobutylicum. This study also investigated the type of sugar that contain in POME, the profile growth rate of C.acetobutylicum and then to investigate consumption of glucose by C. acetobutylicum during fermentation. The experiment works were conducted in schott bottle in anaerobic chamber to maintain anaerobic condition. Fermentation were carried out for 72 hours at 35oC and maintain the concentration of POME (90%) and inoculums concentration (10%) using palm oil mill effluent and reinforced clostridia medium as a substrate in batch culture. The speed that used in this investigation are, 100, 150, 175 and 200 rpm. The result showed that the yield of butanol and ethanol production will increase as the speed increase until it reaches the optimum point (200 rpm). From this study, it was observed that optimum condition for butanol and ethanol fermentation by C. acetobutylicum is at 200 rpm. The concentration of butanol and ethanol from POME for 200 rpm at optimum time (72 hours) is 0.137 g/l and 68.958 g/l respectively. The result of this experiment showed that fresh POME is a viable media for butanol and ethanol fermentation by C. acetobutylicum